Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.jhh.1000745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an angiotensin II receptor antagonist, candesartan cilexetil, on canine intima hyperplasia after balloon injury

Abstract: The roles of angiotensin (Ang) II as produced by two different enzymes, angiotensin-converting enzyme (ACE) and chymase, were investigated in a canine experimental model where intima hyperplasia was induced by balloon catheterization in the common carotid and femoral arteries. The animals received oral candesartan cilexetil (3 mg/kg) or enalapril (10 mg/kg) twice a day for 5 weeks. After 1 week of active drug therapy, the common carotid and femoral arteries were unilaterally injured by balloon catheterization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 15 publications
1
54
0
Order By: Relevance
“…8 These findings are important to understanding of the pathogenesis of endothelial dysfunction observed in cardiovascular disease, because vascular Ang II and ACE are increased in atherosclerotic lesions and restenotic lesions after angioplasty. 18,19,[23][24][25] The present study demonstrated a significant decrease in vascular HGF mRNA in porcine coronary balloon-injured artery, consistent with our previous report. 8 This phenomenon provides the interesting hypothesis that disruption of the autocrine-paracrine local HGF system, which maintains endothelial cell growth, by Ang II may result in abnormal growth of VSMC and endothelial dysfunction, given that endothelial cells secrete antiproliferative substances.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…8 These findings are important to understanding of the pathogenesis of endothelial dysfunction observed in cardiovascular disease, because vascular Ang II and ACE are increased in atherosclerotic lesions and restenotic lesions after angioplasty. 18,19,[23][24][25] The present study demonstrated a significant decrease in vascular HGF mRNA in porcine coronary balloon-injured artery, consistent with our previous report. 8 This phenomenon provides the interesting hypothesis that disruption of the autocrine-paracrine local HGF system, which maintains endothelial cell growth, by Ang II may result in abnormal growth of VSMC and endothelial dysfunction, given that endothelial cells secrete antiproliferative substances.…”
Section: Discussionsupporting
confidence: 81%
“…Negative regulation of local HGF production, probably by Ang II, may play a physiological role in vascular disease, given the activation of the vascular renin angiotensin system in atherosclerosis, restenosis, and hypertension in humans and in experimental models. 18,19,23,24 Figure 5. Effects of perindopril on vasodilator response to bradykinin 28 days after balloon injury (nϭ5 per group).…”
Section: Discussionmentioning
confidence: 99%
“…As might be predicted from this enzyme distribution, candesartan cilexetil significantly suppressed the formation of intimal hyperplasia in both the carotid and femoral arteries, while enalapril significantly suppressed intimal hyperplasia in the femoral but not the carotid arteries. 87 Candesartan cilexetil and enalapril reduced blood pressure almost equally, but enalapril increased plasma renin activity more strongly, and significantly decreased vascular and plasma ACE activities. These results demonstrate that the local production of angiotensin II is involved in the hyperplasia seen in injured intima, and that differences exist in the tissue distribution of the angiotensin II synthetic enzymes, ACE and chymase, which results in a difference in the ability of ACE inhibitors and AIIRAs to prevent hyperplasia in different regions of the vascular system.…”
Section: Pharmacological Properties Of Candesartan Cilexetilmentioning
confidence: 97%
“…Candesartan cilexetil or enalapril were administered to dogs twice daily for 5 weeks. 87 After the first week of active drug therapy, the common carotid and femoral arteries were unilaterally injured by balloon catheterisation. In the common carotid arteries, both ACE and chymase activities increased, with chymase showing the greater increase; in the femoral artery, only ACE was increased by the injury.…”
Section: Pharmacological Properties Of Candesartan Cilexetilmentioning
confidence: 99%
“…However, in clinic, an AT 1 -receptor antagonist, but not an ACE inhibitor, could prevent restenosis after PTCA (13,14). Dog vascular tissues, like humans, contain ACE and chymase as Ang II-forming enzymes, and an AT 1 -receptor antagonist was effective in preventing vascular proliferation after balloon injury and bypass graft in the dog, but an ACE inhibitor was ineffective (15,16). Such species differences in the effect of ACE inhibitor on the proliferation of vascular tissues may depend on whether or not a given species possesses Ang II-forming chymase in vascular tissue.…”
Section: Introductionmentioning
confidence: 98%